การออกแบบต้นแบบตราสัญลักษณ์และกราฟิกบนบรรจุภัณฑ์ให้วิสาหกิจชุมชน กลุ่มคนรักษ์แพะบางบัวทอง ตําบลพิมลราช อําเภอบางบัวทอง โดยใช้วิธีการวิจัยปฏิบัติการแบบมีส่วนร่วม - ธนัทพรรษรัตน์, ปัณณ์ณัช (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2017)
The study of Logo and Graphic Prototype Designs on Packaging for the Community Enterprise called Bang Bua Thong Goat Lovers in Tambon Pimolraj, Ampher Bang Bua Thong is a participatory Action Research which aimed to 1) survey problems and demands in the development of logo and graphic prototypes on packaging of the enterprise, 2) develop logo and graphic prototypes on packaging for the enterprise, and 3) study consumers’ satisfactions toward the logos and graphics and the packaging of the enterprise. The population and samples consisted of 1) 18 members of the Community Enterprise Bang Bua Thong Goat Lovers and 2 Livestock Officers of Nonthaburi Province gained by Purposive Sampling, 2) 3 logo experts and 3 packaging graphic experts, 3) 200 consumers – to study their satisfactions toward the logos and graphics on packaging – gained by Accidental Sampling within 5 months after the product release. The research tools consisted of questions for focus group, ranking questionnaire for logo and graphic selection, and questionnaire for consumers’ satisfactions toward the logos. The data was analyzed by percentage and Mean. The research results revealed as follows. 1) The problem of Community Enterprise Bang Bua Thong Goat Lovers was lacking of logos and graphics on packaging which resulted in demanding the development of logos and graphics on their 13 kinds of packaging. 2) From the engaging process between the researcher and the enterprise, it was found that the enterprise wanted to name their group “Iris Nature” which came from the Chairperson of the enterprise. They chose to use combination logos to convey clear meanings by cutting from the goat that won the prize of National Goat Contest. The graphics on the packaging were clipped out pictures to convey the natural goat raising. The colors looked luxurious to add more values on the products. 3) The consumers’ satisfactions toward the logos were in high level in the following aspects; Easy to Remember, Identity, Outstanding, and Colors Consistent with Products. Also, their satisfactions toward the 13 kinds of packaging and the graphics on them were all in high level as well.